Preliminary Study of Grade Five Students’ Critical Thinking Skills on Plants Material - Laudia, Stefanie Marla; Widodo, Wahono; Sudibyo, Elok; Prahani, Binar Kurnia (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2023)
This study investigated the initial critical thinking skills of grade five students on plant materials and explored a suitable learning model solution method for the students' conditions. The study used a preliminary design and a critical thinking skills test instrument to collect data. The results showed that students' critical thinking skills varied widely, with none of the students scoring in the very good category, 11.00% of students scoring in the good category, 58.00% of students scoring in the fair category, 26.00% of students scoring in the poor category, and 5.00% of students scoring in the very poor category. These findings suggest that students need more support to develop their critical thinking skills, particularly in the areas of deduction, inference, and evaluation of arguments. Future researchers could design learning tools using specific learning methods/models to address these areas and improve students' critical thinking skills.